A molecular switch in sulfur metabolism to reduce arsenic and enrich selenium in rice grain - Sheng-Kai Sun (Nature Portfolio, 2021)
Contamination of paddy soils can lead to toxic arsenic accumulation in rice grains and low levels of the micronutrient selenium. Here the authors show that a gain of function mutant affecting an O-acetylserine (thiol) lyase enhances sulfur and selenium assimilation while reducing arsenic accumulation in grains.